On the foliation of space-time by constant mean curvature hypersurfaces - Gerhardt, Claus (Arxiv, 2003)
We prove that the mean curvature [tau] of the slices given by a constant mean curvature foliation can be used as a time function, i.e. [tau] is smooth with non-vanishing gradient.